Pengetahuan Masyarakat Mengenai Keberadaan Ikan Capungan Banggai Pterapogon Kauderni Koumans, 1933 (Perciformes, Apogonidae) Di Teluk Palu Sulawesi Tengah - Andhy Rahmat Padyawan Unok; Rasul Rasul; Hartina Hartina; Yuliana Yuliana; Abdul Waris; Samliok Ndobe; Yahya Rizkiandra Suryatama; Moh. Fahrit W Hein; Nurhikmah Nurhikmah; Muhammad Herjayanto (Universitas Mataram, 2024)
The Banggai cardinalfish, known internationally as the Banggai cardinalfish, is an endemic species of the Banggai Archipelago and its surrounding marine waters. In general, the public's understanding of the existence and conservation efforts for this fish is limited due to a lack of access to information and education about the species. Public knowledge about the existence of the Banggai cardinalfish is a crucial factor in the success of conservation programs. One of the introduction habitats for the Banggai cardinalfish is the waters of Teluk Palu. The purpose of this research is to explore the level of knowledge and perceptions of the community regarding the presence of the Banggai cardinalfish in Teluk Palu. The sampling method used is purposive sampling, obtaining primary data through field observations, questionnaires, in-depth interviews, and research documentation. Secondary data were obtained from online scientific reference searches. Data analysis used includes descriptive and qualitative analysis. The research results show that the knowledge and understanding of the Teluk Palu community about the existence and conservation of the Banggai cardinalfish still require significant improvement. Through education, community involvement, and the provision of sustainable livelihood alternatives.